The Montreal Cognitive Assessment (MoCA-Ina) versus the Mini-Mental State Examination (MMSE-Ina) For Detecting Mild Cognitive Impairment among The Elderly (Bangladesh Journal of Medical Science, 2021)
Background: There are many neuropsychological instruments are used for screening cognitivefunctions in adults, with or without health problems such asthe MMSE-Ina and MoCA-Ina.Objectives:This study was designed to test the correlations and differences between MMSE-Inaand MoCA-Ina for early detection of decreasing cognitive function in the elderly.Methods: Total278 subjects were randomly selected from the 17 sub dictricts of Surakarta Municipality, CentralJava, Indonesia. Data collection was carried out in December 2018 and January 2019, withallsubjects individually interviewed using two cognitive tests (which lasted 30 – 45 minutes) alongwith physical and neurological examinations. The MMSE-Ina and MoCA-Ina scores of eachparticipant were correlated using the non-parametric Spearman rank test. Both scores werecompared based on level of education and gender.Results: The MoCa-Ina detected using MCIwas 215 (77.3%) while MMSE-Ina was 189 (68%), with 176 (63.3%) in severe 10 (3.5%).This study also showed a strong correlation between the MMSE-Ina and MoCA-Ina scores (r= 0.633 p < 0.000). The cut pointin this study were 23/24 for the MMSE-Ina and 25/26 for theMoCA-Ina which was less than 23 and 25,indicated cognitive impairment.Conclusion: TheMoCA-Ina is usedto screen cognitive impairment in the elderly.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.164-169